Taxonomy and ecology of genus Phlogophora Treitschke, 1825 (Lepidoptera: Noctuidae) in Indian Himalaya with description of a new species - Bandyopadhyay, Uttaran; Dey, Rushati; Bhattacharyya, Kamalika; Mallick, Kaushik; Mazumder, Arna; Gayen, Subrata; Das, Moumita; Raha, Angshuman; Sanyal, Abesh Kumar; Kumar, Vikas; Uniyal, Virendra Prasad; Chandra, Kailash (Zootaxa, 2021)
The Genus Phlogophora Treitschke, 1825 (Noctuidae: Xyleninae), widely distributed in Palaearctic and Oriental realms, is especially diverse within Indian Himalaya with 12 known species till now. Current communication reports three species new to India viz. P. meticulodina (Draudt, 1950), P. nobilis Hreblay & Ronkay, 1998 and P. szecsenyii Hreblay & Ronkay, 1998 and a new species P. similis Bandyopadhyay, Mallick, Sanyal & Chandra sp. nov., thus bringing the species number to 16 for the country, along with taxonomic key with morphology and genitalia-based diagnosis for all the Indian/Himalayan species. Out of those species, partial mitochondrial Cytochrome C Oxidase I (COI) sequences were generated for 6 species, of which 5 were novel to the NCBI GenBank. The genus had maximum species richness and abundance in Eastern Himalayan Temperate Forest spanning 1800–2500 m in Central Himalayan landscape of Darjeeling-Sikkim and Nepal. Current Habitat suitability model of six Phlogophora species indicated that temperature dependent variables like Temperature Annual Range, Temperature Seasonality and Elevation are the most contributing factors for their predicted distribution range. The genus comprising of both Polycyclic and Monocyclic species became most abundant during Post-monsoon, in cold (9–11 ºC) and humid (87–91%) nights, in areas with Annual Mean Temperature ranging within 4.6–19.9 ºC and Annual Precipitation of 1000–2800 mm.